Optimal Hypoxia Regulates Human iPSC-Derived Liver Bud Differentiation through Intercellular TGFB Signaling - Hiroaki Ayabe (Stem Cell Reports, 2018)
Summary: Timely controlled oxygen (O2) delivery is crucial for the developing liver. However, the influence of O2 on intercellular communication during hepatogenesis is unclear. Using a human induced pluripotent stem cell-derived liver bud (hiPSC-LB) model, we found hypoxia induced with an O2-permeable plate promoted hepatic differentiation accompanied by TGFB1 and TGFB3 suppression. Conversely, extensive hypoxia generated with an O2-non-permeable plate elevated TGFBs and cholangiocyte marker expression. Single-cell RNA sequencing revealed that TGFB1 and TGFB3 are primarily expressed in the human liver mesenchyme and endothelium similar to in the hiPSC-LBs. Stromal cell-specific RNA interferences indicated the importance of TGFB signaling for hepatocytic differentiation in hiPSC-LB. Consistently, during mouse liver development, the Hif1a-mediated developmental hypoxic response is positively correlated with TGFB1 expression. These data provide insights into the mechanism that hypoxia-stimulated signals in mesenchyme and endothelium, likely through TGFB1, promote hepatoblast differentiation prior to fetal circulation establishment. : To delineate the influence of O2 on liver development, human induced pluripotent stem cell-derived liver buds were used as a fetal liver model. This model provides insight into hypoxic modulation of mesenchyme-derived TGFB signals that promote hepatoblast differentiation in developing liver buds prior to blood circulation. Keywords: liver bud, organogenesis, organoid, oxygen, iPSC, differentiation, hypoxia